Implementation of Marketing Mix in Improving Brand Image: Case Study on Bakso Mas Roy in Surabaya City, Merr Branch - Varadisa, Adelia Qouli; Kusuma, Yanda Bara (Jurnal Manajemen Bisnis, 2024)
Bakso Mas Roy Merr branch is a meatball culinary business known for its unique flourless meatballs, designed to attract consumers with a distinctive taste. This study aims to describe the implementation of the 4P marketing mix at Bakso Mas Roy Merr branch for developing and enhancing its brand image. The research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. Data analysis involves data reduction, data presentation, and drawing conclusions. The findings indicate that while the 4P marketing mix is applied to improve the brand image, some aspects remain ineffective. Challenges in the implementation of the 4P marketing mix at the Merr branch are noted in the Product and Price factors, while the Place and Promotion factors are considered supportive. As the factors examined in this study are limited, future research should explore the 4P marketing mix more broadly using diverse techniques